Pitfalls of Scientific Forestry Practices in the Community Forestry of Nepal - Basnyat, Bijendra (FORESTRY: Journal of Institute of Forestry, Nepal, 2021)
The government of Nepal abolished scientific forest management in 2021, however, the underlying reason remained unexplored. Hence, this study explores reasons that pushed on abolishment of this practice in the community forestry. The study followed the qualitative methods and reviewed the policy documents, published and unpublished literature followed by semi-structured interviews with forest officials and community forestry leaders. Though scientific forest management was promoted to maximize timber production and employment generation, stakeholders often raised concern over the exploitation of forests, including the appropriateness of the proposed silviculture system along with the governance issues related to it. On the contrary, forest bureaucracy promoted this as an “one size fit approach” irrespective of management objectives while poorly integrating locality factors, and research-generated knowledge. Apparently, scientific forest management is highly contested on technical and managerial grounds, while it is utterly uneconomical to forest user groups. Diverse views, interests and disbelief of the stakeholders, along with inadequate scientific evidence is primary reasons for a failure. Hence, the study argues for promoting “research in use approach” in strengthening forest management practices with the wider engagement of the stakeholders from knowledge generation, use, and dissemination in the community forestry.